(untitled) (Seminário Internacional de Informação, Tecnologia e Inovação, 2024)
Accessibility and inclusion reflects a commitment to equal opportunities for all those at the University. Thus, the objective of this work was to carry out a study on the use of the Accessibility Laboratory at the Federal University of Alagoas between the years 2022 and 2023. Research classified as exploratory, bibliographical and documentary research and a quantitative approach were established as procedures. The results obtained indicated a greater request for services in the year 2022, the users who used the services most were servers and the most used service was the adaptation of teaching material.